Study on spatial correlation and driving factors of industrial carbon emission in the Hefei metropolitan area based on SNA-QAP method - Dawei Dai; Yuewen Liu; Shuhang Zhao; Yue Chen (Scientific Reports)
Abstract In this paper, the Hefei metropolitan area is selected as the research object to measure industrial carbon emissions in this area during 2010–2022. The main contribution is to deeply analyze the characteristics of the spatial correlation network of industrial carbon emissions in the Hefei metropolitan area with the modified gravity model and social network analysis(SNA), and to explore the driving factors of its formation with quadratic assignment procedure(QAP). It establishes the foundation for the Hefei metropolitan area to differentiated green city development policies. The results show that (1) The industrial carbon emission in the Hefei metropolitan area showed a fluctuating and rising trend, forming a strongly connected carbon emission network spatial patterna; (2) The overall structure of the spatial correlation network of industrial carbon emissions in the Hefei metropolitan area is stable, but the tightness of the spatial correlation relationship among cities is not enough and the hierarchy is evident; (3) Hefei and Huainan are the centers of the carbon emission spatial correlation network of the Hefei metropolitan area, the position of each city in the carbon emission spatial correlation network is obviously unbalanced; (4) Urbanization level, economic development level, technological innovation, level of opening up and industrial structure exert considerable influence on the establishment and evolution of the spatial correlation network pertaining to industrial carbon emissions within the Hefei metropolitan area.